2015
DOI: 10.1111/fwb.12678
|View full text |Cite
|
Sign up to set email alerts
|

Are high densities of fishes and shrimp associated with top‐down control of tropical benthic communities? A test in three Hong Kong streams

Abstract: Summary Top‐down control of benthic communities by fishes in temperate and Neotropical streams has received considerable attention, yet relatively little is known about the occurrence or strength of such top‐down control in tropical Asian streams. We undertook pool‐scale removals of an entire macroconsumer assemblage of fishes and predatory shrimp, as well as its component guilds (algivores versus predators), in three Hong Kong streams during the dry season and monitored the responses of periphyton, benthic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 73 publications
(124 reference statements)
2
10
0
Order By: Relevance
“…One explanation is that the macroinvertebrates consistently evaded fish and shrimp predators; this has been shown in studies that artificially doubled the natural densities of fish and failed to observe a decrease in some invertebrate taxa (Gilliam et al, 1989;Dudgeon, 1991). Our study also did not reveal a consistent pattern in macroinvertebrate diversity of above-and below-waterfall pools, suggesting that communities of shrimp and fish do not influence these biotic patterns; however, it is possible that fish and shrimp predators are substitutable and thus functionally redundant (sensu Ho & Dudgeon, 2016). In Northern Australia, Garcia et al (2015) found that top-down effects on macroinvertebrates were context dependent with respect to factors such as benthic habitat, stream velocity and community structure, each of which influenced invertebrate diversity.…”
Section: Discussionsupporting
confidence: 44%
See 4 more Smart Citations
“…One explanation is that the macroinvertebrates consistently evaded fish and shrimp predators; this has been shown in studies that artificially doubled the natural densities of fish and failed to observe a decrease in some invertebrate taxa (Gilliam et al, 1989;Dudgeon, 1991). Our study also did not reveal a consistent pattern in macroinvertebrate diversity of above-and below-waterfall pools, suggesting that communities of shrimp and fish do not influence these biotic patterns; however, it is possible that fish and shrimp predators are substitutable and thus functionally redundant (sensu Ho & Dudgeon, 2016). In Northern Australia, Garcia et al (2015) found that top-down effects on macroinvertebrates were context dependent with respect to factors such as benthic habitat, stream velocity and community structure, each of which influenced invertebrate diversity.…”
Section: Discussionsupporting
confidence: 44%
“…Moulton et al (2010) found that predacious fish inhibit shrimp and baetid mayflies from grazing in two Neotropical streams, thus increasing both abundance and quality of periphyton in pools containing fish. However, other experiments have found that top-down effects of fish on algae have less impact relative to bottom-up effects such as increases in nutrient levels (Garcia et al, 2015;Ho & Dudgeon, 2016). Interestingly, Ho & Dudgeon (2016) found no impact of high numbers of fish and shrimp on algal biomass or periphyton accumulation in three Hong Kong streams.…”
Section: Ecosystem Functionsmentioning
confidence: 85%
See 3 more Smart Citations